2009
DOI: 10.1038/ismej.2009.91
|View full text |Cite
|
Sign up to set email alerts
|

Linking phylogenetic and functional diversity to nutrient spiraling in microbial mats from Lower Kane Cave (USA)

Abstract: Microbial mats in sulfidic cave streams offer unique opportunities to study redox-based biogeochemical nutrient cycles. Previous work from Lower Kane Cave, Wyoming, USA, focused on the aerobic portion of microbial mats, dominated by putative chemolithoautotrophic, sulfuroxidizing groups within the Epsilonproteobacteria and Gammaproteobacteria. To evaluate nutrient cycling and turnover within the whole mat system, a multidisciplinary strategy was used to characterize the anaerobic portion of the mats, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 60 publications
2
41
0
2
Order By: Relevance
“…Localized variations in geochemistry and nutrient availability have been shown to impact microbial community structure (Johnston et al, 2012;Barton and Jurado, 2007;Shabarova and Pernthaler, 2010) and niche diversification (Engel et al, 2010;Macalady et al, 2008). Further, the composition of cave microbial communities mediates and stabilizes biogeochemical cycling and mineralization processes within an environment (Portillo and Gonzalez, 2010;Portillo et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Localized variations in geochemistry and nutrient availability have been shown to impact microbial community structure (Johnston et al, 2012;Barton and Jurado, 2007;Shabarova and Pernthaler, 2010) and niche diversification (Engel et al, 2010;Macalady et al, 2008). Further, the composition of cave microbial communities mediates and stabilizes biogeochemical cycling and mineralization processes within an environment (Portillo and Gonzalez, 2010;Portillo et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Given the metabolic flexibility of pseudomonads to degrade complex organic molecules in the environment, the acquisition of these genes suggests that HGT may have expanded the cellular catabolic pathways to take advantage of presumably microbial detritus within the system, allowing this organism to play a potentially important role in carbon turnover. Indeed, in a number of cave systems, geologic isolation has led to the evolution of microbial ecosystems more dependent on chemolithotrophic energy generation and bacterially derived carbon turnover than similar microbial systems in soils (62). Nonetheless, many of the genes in these genomic islands had no annotated homologs in sequence databases, suggesting that the full range of adaptations by P. fluorescens R124 remains to be elucidated, an unsurprising finding given that the sequencing of greater numbers of genomes reveals increasingly greater numbers of gene families (63).…”
Section: Discussionmentioning
confidence: 99%
“…Clone sequences affiliated with the genus Sphingomonas were also retrieved from all wells. From the clone libraries, Girl Scout Deep and Paradise Alley Shallow shared an OTU that was most closely related to uncultured Alphaproteobacteria (99% sequence similarity) isolated from the sulfidic Lower Kane Cave, Wyoming, USA (Engel et al, 2010). In contrast, pyrosequence results showed that Caulobacteraceae were rare (o0.3% of all pyrosequences for any sample), Sphingomonadales were only retrieved from freshwater wells and Comal Springs, and representation by Rhodospirillales or Rhizobiales families was higher (up to 12%) in all wells (Supplementary Table S3).…”
Section: Taxonomic Diversitymentioning
confidence: 99%